Pelaksanaan Metode Uswah Hasanah pada Mata Pelajaran Akidah Akhlak - Izzi Fekrat; Martin Kustati; Rezki Amelia (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This article aims to look at the phenomenon of educators in the use of learning methods, because educators are one of the final factors in the success or failure of learning carried out in schools, so by using a variety of teaching methods students are expected to achieve maximum learning achievement. One of the learning methods that can be applied in Akidah Akhlak learning is the Uswah Hasanah method. This method as a method is used to realize educational goals by giving good exemplary examples to students to be in line with the values of the Qur'an and Sunnah. The purpose of this research is to explain the planning, implementation, evaluation, and supporting and inhibiting factors. The type of research is descriptive qualitative field research. Descriptive type is a research intended to collect information about the status of an existing symptom, namely the state of the symptom according to what it is at the time the research is conducted. The results showed that the planning of the Uswah Hasanah method in Akidah Akhlak had been made by educators and had been applied in the learning process. The planning is in the form of a teaching module. The implementation has been carried out in accordance with the planning made in the teaching module, although the implementation is not in accordance with the actual theory and not all steps of using the method are carried out by Akidah Akhlak educators. Evaluation of the implementation of this method is carried out continuously during learning.